Aboriginal Representation: Conflict or Dialogue in the Academy - Leane, Jeanine (The Australian Journal of Indigenous Education, 2010)
Abstract This research begins with the premise that non-Aboriginal students are challenged by much Aboriginal writing and also challenge its representations as they struggle to re-position themselves in relation to possible meanings within Aboriginal writing. Many non-Aboriginal students come to read an Aboriginal narrative against their understanding of what it means to be an Aboriginal Australian, accumulated via their prior reading of Australian history, literature and more contemporary social analysis and popular commentary. Aboriginal writing is confronting when it disturbs the more familiar representations of Aboriginal experience and characterisation previously encountered. The aim of this paper is to provide a more informed basis from which to consider higher education pedagogy for this area of literary studies. A further aim is to contribute to the literary studies discourse on Aboriginal representation in Australian literature.